Membrane Association Landscape of Myelin Basic Protein Portrays Formation of the Myelin Major Dense Line - Arne Raasakka (Nature Portfolio, 2017)
Abstract Compact myelin comprises most of the dry weight of myelin, and its insulative nature is the basis for saltatory conduction of nerve impulses. The major dense line (MDL) is a 3-nm compartment between two cytoplasmic leaflets of stacked myelin membranes, mostly occupied by a myelin basic protein (MBP) phase. MBP is an abundant myelin protein involved in demyelinating diseases, such as multiple sclerosis. The association of MBP with lipid membranes has been studied for decades, but the MBP-driven formation of the MDL remains elusive at the biomolecular level. We employed complementary biophysical methods, including atomic force microscopy, cryo-electron microscopy, and neutron scattering, to investigate the formation of membrane stacks all the way from MBP binding onto a single membrane leaflet to the organisation of a stable MDL. Our results support the formation of an amorphous protein phase of MBP between two membrane bilayers and provide a molecular model for MDL formation during myelination, which is of importance when understanding myelin assembly and demyelinating conditions.